Expression of vaccinia-related kinase 1 (VRK1) accelerates cell proliferation but overcomes cell adhesion mediated drug resistance (CAM-DR) in multiple myeloma. Issue 10 (25th November 2016) - Liu, Jing; Wang, Yuchan; He, Song; Xu, Xiaohong; Huang, Yuejiao; Tang, Jie; Wu, Yaxun; Miao, Xiaobing; He, Yunhua; Wang, Qiru; Liang, Li; Cheng, Chun
Abstract : Objective : Vaccinia-related kinase 1 (VRK1) has been reported to participate in the development of a variety of tumors. However, the role of VRK1 in multiple myeloma (MM) has not been investigated. The present study was undertaken to determine the expression and biologic function of VRK1 in human MM. Methods : First, we constructed a model of cell adhesion in MM, the mRNA and protein level of VRK1 in suspension and adhesion model was analyzed by RT-PCR and western blot. Then, flow cytometry assay and western blot were used to investigate the mechanism of VRK1 in the proliferation of MM cells. In vitro, following using shRNA interfering VRK1 expression, we performed adhesion assay and cell viability assay to determine the effect of VRK1 on adhesive rate and drug sensitivity. Results : VRK1 was lowly expressed in adherent MM cells and highly expressed in suspended cells. In addition, VRK1 was positively correlated with the proliferation of MM cells by regulating the expression of cell cycle-related protein, such as cyclinD1, CDK2 and p27 kip1 . Furthermore, VRK1 could reverse cell adhesion mediated drug resistance (CAM-DR) by down-regulating the ability of cell adhesion. Conclusion and discussion : Our data supports a role for VRK1 in MM cell proliferation, adhesion, and drug resistance, and it may pave the way for a novel therapeutic approach for CAM-DR in MM.